Oxygen Tension in Blood, Skeletal Muscles and Tissue Metabolism Peculiarities of Liza aurata Risso Under Experimental Hypothermia - Soldatov, A. A.; Parfyonova, I. A. (Problems of Cryobiology and Cryomedicine, 2009)
Influence of temperature within 1...15°С range on oxygen tension and metabolic processes orientation in skeletal muscles of Liza aurata Risso was investigated under experiment conditions. It was shown, that hypothermia (5°С and lower) caused the development of tissue hypoxia. This phenomenon was of secondary character and was connected with increase of number hypoxic zones in a muscular tissue, decrease muscle and venous РO2. It resulted to activation of anaerobic in muscles. It reflects a rise of the lactate content, decrease of ATP level and also fall of pH value in venous blood. At temperatures close to 5°С in a mullet organism marked development of compensation processes. They have been shown in full or partial restoration РO2 in muscles and venous blood at parallel suppression anaerobic processes. Their efficiency was lost with temperature fall. At 1...2°С they were not revealed at all.